Pengaruh Pendekatan Contextual Teaching And Learning CTL Terhadap Hasil Belajar IPAS Siswa Kelas V SDN Majungan - Sitti Norkholizah; Isna Ida Mardiyana (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The pupose of this study was to determine the significant effect of the Contextual Teaching and Learning (CTL) approach in the learning outcomes of IPAS grade V students of SDN Majungan. The research design used in this research is Pre-Eksperimental with the form of One-Group Pretest-Posttest Design. This study used a saturated sampling technique with a total size of 22 students. Data collection in this study used observation, test, and documentation. The results of this study indicate that the CTL approach has an effect on the learning outcomes of fifth grade SDN Majungan. Based on the calculation of hypothesis test with the paired sample t-test, obtained thitung is -20,014 and ttabel is -2,085 a significance value of 0,000. Based on left-sided test criteria, if -thitung < -ttabel is -20,014 < -2,085 then H1 is accepted and H0 is rejected. On the results of Sig. 2(tailed) < 0,05 (0,000 < 0,05) then H0 is rejected and H1 is accepted, which means that there is an effect on the Contextual Teaching and Learning (CTL) approach on students IPAS learning outcomes. The implementation of learning with Contextual Teaching and Learning approach was carried out with very good criteria with an average of 92.